The use of polylactic and polyglycolic copolymer biomaterial in a pre-clinical model of compromised primary stability - Kayatt, Fernando E.; Queiroz, Thallita P.; Margonar, Rogério; Luvizuto, Eloá R. [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Okamoto, Roberta [UNESP] (My University, 2013)
Aim Primary implant stability can be compromised by overdrilling of the implant bed. Filling the gap between the implant and the bone with a highly viscous copolymer of polylactic and polyglycolic acid (PLA/PGA) might stabilize the implant and thus supply osseointegration. The aim of this study was to evaluate implants installed in overdrilled beds associated with PLA/PGA in rats tibia model by means of removal torque test and fluorochrome analysis. Materials and methods For this experiment two groups were selected: in the test group 0.4 mm overdrilled defects (2.0 in diameter and 3 mm long ) were produced in the right tibia of seven rats and implants were placed covered with PLA/PGA biomaterial to fill the gap; the control group was not overdrilled and the implants were placed without the biomaterial. Implants of 1.6 mm in diameter and 3 mm long where placed into all defects. Calcein, alizarin and oxytetracyclin were injected at 7, 15 and 21 postoperative days, respectively, and the animals were sacrificed at 35 postoperative day. Results The results showed that all the implants achieved osseointegration. There were no statistical significance differences in torque-reverse and fluorocrome analysis (P>0.05). Conclusion We can conclude that overdrilled defects filled with PLA/PGA did not disturb osseointegration in this experimental model. © ARIESDUE.
Keywords: Bone remodeling; Dental implants; Fluorochrome; Osseointegration; Polyglycolic acid; Polylactic acid